Sales Promotion and Personal Selling in Support of Integrated Marketing Strategy - Ekasari, Silvia; Yanna, Sri; Wakhidah, Esti Nur; Achmad, Gusti Noorlitaria; Munizu, Musran (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
At this time, marketing activities have a very important role in the business world, and are even the key to business success. Strategy is essentially planning and management to achieve a goal. However, to achieve these goals, strategy does not function as a roadmap that only shows how operational tactics are. Likewise with the strategy which is a guide to communication planning to achieve predetermined goals. The purpose of this study is to discuss how far sales promotion and personal selling in support of integrated marketing strategy. The research uses a literature review. The type of data used is secondary data. The data collection method is a literature study. Integrated marketing includes coordination efforts through communication of various promotional elements and other marketing activities through an integrated marketing strategy in the form of sales promotion and personal selling.